2: INTRODUCTION OF RIO GRANDE TURKEYS INTO KANSAS* - Stephen W. Capel (Wildlife Society Bulletin)
ABSTRACT In the late 1950's, a few Rio Grande turkeys (Meleagris gallopavo intermedia) emigrated into Kansas from Oklahoma, but early trapping efforts within Kansas were fragmented, and transplants met with failure. In 1966 and 1967, trades with Texas and Oklahoma brought 161 wild‐trapped Rio Grande turkeys to Kansas for release at 14 sites. In 1968, Kansas adopted the drop‐net trapping technique, which had been 'developed in Oklahoma, and trapped 82 turkeys for transplanting purposes during 1968 and 1969. To date, a total of 22 transplants and 6 supplemental releases have been made throughout Kansas, employing 278 wild‐trapped Rio Grande turkeys from Kansas, Oklahoma, and Texas. Winter flock counts during the winter of 1968‐69 indicated a minimum of 489 turkeys at 23 release sites. In south‐central and southwest Kansas, transplants have usually proven successful, with populations of 90, 76, and 60 birds resulting from releases of 12 birds each at the three most successful sites. The turkeys have fared poorly in both eastern and northern Kansas. Precipitation in excess of 30 inches per year appears to be detrimental to reproduction in eastern Kansas, but no reason can be advanced for the poor success observed in northern Kansas. At four sites, subadults were the only males released. Broods were produced at three of the four sites the first summer. Breeding chronology at these three sites appeared to be the same as the general hatch curve for the state. The future of Rio Grande turkeys in Kansas is bright provided that stream channeling and timber clearing, which destroy the prime habitat along the creeks, do not increase markedly.